2015
DOI: 10.1039/c5ra09364c
|View full text |Cite
|
Sign up to set email alerts
|

Applications of supramolecular capsules derived from resorcin[4]arenes, calix[n]arenes and metallo-ligands: from biology to catalysis

Abstract: Supramolecular architectures developed after the initial studies of Cram, Lehn and Pedersen have become structurally complex but fascinating. In this context, supramolecular capsules based on resorcin[4]arenes, calix[n]arenes or metal-ligand structures are dynamic assemblies inspired by biological systems. The reversible formation of these assemblies, combined with the possibility to modify their dimensions and shapes in the presence of a guest (concepts of reversibility and adaptivity) make them similar to bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(22 citation statements)
references
References 168 publications
(189 reference statements)
0
22
0
Order By: Relevance
“…[74g],[88] Although the precise nature of the interactions between these cationic organometallic complexes and the cavity of the supramolecular host requires further elucidation, the potential for these encapsulated catalyst systems to enable both enthalpic and entropic transition-state stabilization offers tantalizing opportunities for future development.…”
Section: Catalyst–substrate Cation–π Interactionsmentioning
confidence: 99%
“…[74g],[88] Although the precise nature of the interactions between these cationic organometallic complexes and the cavity of the supramolecular host requires further elucidation, the potential for these encapsulated catalyst systems to enable both enthalpic and entropic transition-state stabilization offers tantalizing opportunities for future development.…”
Section: Catalyst–substrate Cation–π Interactionsmentioning
confidence: 99%
“…able to generate bowlso rc apsules by means of weak host-guest interactions. [7] Metallacages, based on coordination chemistry tools, have been obtainedb yt he self-assembly of cations and organic linkersa nd usuallya nionic encapsulationi so bserved, profitingf rom its cationic character. [8,9] Arecent advance in this field consist of the multi-guest systems built from heterotopic hosts exhibiting endo-exo linkings ites that, in the best of the cases, can promote allostericeffects.…”
Section: Introductionmentioning
confidence: 99%
“…In 2015, a comprehensive review reported the applications of some nanocontainers in the catalytic field [9]. Thus, this review is focused on the recent catalytic applications to date since 2015.…”
Section: Introductionmentioning
confidence: 99%